Hyaluronic acid-shelled acid-activatable paclitaxel prodrug micelles effectively target and treat CD44-overexpressing human breast tumor xenografts in vivo. (April 2016) - Zhong, Yinan; Goltsche, Katharina; Cheng, Liang; Xie, Fang; Meng, Fenghua; Deng, Chao; Zhong, Zhiyuan; Haag, Rainer
Abstract: The therapeutic efficacy of nanoscale anticancer drug delivery systems is severely truncated by their low tumor-targetability and inefficient drug release at the target site. Here, we report the design and development of novel endosomal pH-activatable paclitaxel prodrug micelles based on hyaluronic acid- b -dendritic oligoglycerol (HA-dOG-PTX-PM) for active targeting and effective treatment of CD44-overexpressing human breast cancer xenografts in nude mice. HA-dOG-PTX-PM had a high drug content of 20.6 wt .% and an average diameter of 155 nm. The release of PTX was slow at pH 7.4 but greatly accelerated at endosomal pH. MTT assays, flow cytometry and confocal experiments showed that HA-dOG-PTX-PM possessed a high targetability and antitumor activity toward CD44 receptor overexpressing MCF-7 human breast cancer cells. The in vivo pharmacokinetics and biodistribution studies showed that HA-dOG-PTX-PM had a prolonged circulation time in the nude mice and a remarkably high accumulation in the MCF-7 tumor (6.19%ID/g at 12 h post injection). Interestingly, HA-dOG-PTX-PM could effectively treat mice bearing MCF-7 human breast tumor xenografts with little side effects, resulting in complete inhibition of tumor growth and a 100% survival rate over an experimental period of 55 days. These results indicate that hyaluronic acid-shelled acid-activatable PTX prodrug micelles have a great potential for targeted chemotherapy of CD44-positive cancers.